Why unions reduce wage inequality, II: the relation between solidarity and unity - Stennek, Johan (Gothenburg, 2015)
"This paper demonstrates that the decisions by workers of different skills to unite to form industry unions is closely linked to the egalitarian wage policies that such unions pursue. These results help interpret the stylized facts about unions: that they not only increase wages but also reduce wage inequality. I also demonstrate that political caps on collectively negotiated minimum wages may reduce the wages of all blue-collar workers (cf. “internal devaluation”), but that they may also cause unions to disintegrate in the long run."